Machine learning with in silico analysis markedly improves survival prediction modeling in colon cancer patients. (7th November 2022) - Lee, Choong‐Jae; Baek, Bin; Cho, Sang Hee; Jang, Tae‐Young; Jeon, So‐El; Lee, Sunjae; Lee, Hyunju; Nam, Jeong‐Seok
Abstract: Background: Predicting the survival of cancer patients provides prognostic information and therapeutic guidance. However, improved prediction models are needed for use in diagnosis and treatment. Objective: This study aimed to identify genomic prognostic biomarkers related to colon cancer (CC) based on computational data and to develop survival prediction models. Methods: We performed machine‐learning (ML) analysis to screen pathogenic survival‐related driver genes related to patient prognosis by integrating copy number variation and gene expression data. Moreover, in silico system analysis was performed to clinically assess data from ML analysis, and we identified RABGAP1L, MYH9, and DRD4 as candidate genes. These three genes and tumor stages were used to generate survival prediction models. Moreover, the genes were validated by experimental and clinical analyses, and the theranostic application of the survival prediction models was assessed. Results: RABGAP1L, MYH9, and DRD4 were identified as survival‐related candidate genes by ML and in silico system analysis. The survival prediction model using the expression of the three genes showed higher predictive performance when applied to predict the prognosis of CC patients. A series of functional analyses revealed that each knockdown of three genes reduced the protumor activity of CC cells. In particular, validation with an independent cohort of CC patients confirmed that the coexpression of MYH9 and DRD4 gene expression reflected poorer clinical outcomes in terms of overall survival and disease‐free survival. Conclusions: Our survival prediction approach will contribute to providing information on patients and developing a therapeutic strategy for CC patients.